Criminal legalities in the global South : cultural dynamics, political tensions, and institutional practices - Ciocchini, Pablo Leandro, 1978-; Radics, George Baylon, 1979- (Routledge studies in crime and justice in Asia and the global South., 2020)
"This book presents the work of academics from the Global South and explores, from local and regional settings, how the legal order and people's perception of it translates into an understanding of what constitutes 'criminal' behaviours or activities. It aims to make an important contribution in the development of Southern Criminology"--